2004
DOI: 10.1038/sj.ijir.3901208
|View full text |Cite
|
Sign up to set email alerts
|

Potency, selectivity, and consequences of nonselectivity of PDE inhibition

Abstract: Phosphodiesterases (PDEs) play a decisive role in cyclic nucleotide-mediated intracellular signaling. As PDEs are expressed in a variety of tissues, selectivity is a prerequisite for a therapeutically applicable PDE inhibitor. Sildenafil, vardenafil, and tadalafil are selective for PDE5, with vardenafil exhibiting the highest potency and minimal inhibition of other PDEs, with the exception of PDE6. Tadalafil is extremely selective for PDE5, but also potently inhibits PDE11, an enzyme with unknown physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
171
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 8 publications
6
171
0
Order By: Relevance
“…10,13 It has been suggested that elevated levels of cGMP, caused by PDE5 inhibitors, could inhibit PDE3, an enzyme responsible for the hydrolysis of cyclic adenosine monophosphate (cAMP) and increase cAMP levels, resulting in elevated HR and contractility. 19 Our results showed that tadalafil did not increase HR nor induce arrhythmias.…”
Section: Discussionmentioning
confidence: 55%
“…10,13 It has been suggested that elevated levels of cGMP, caused by PDE5 inhibitors, could inhibit PDE3, an enzyme responsible for the hydrolysis of cyclic adenosine monophosphate (cAMP) and increase cAMP levels, resulting in elevated HR and contractility. 19 Our results showed that tadalafil did not increase HR nor induce arrhythmias.…”
Section: Discussionmentioning
confidence: 55%
“…Vardenafil, a highly selective PDE5A inhibitor is an on‐demand treatment for erectile dysfunction and it displays the highest potency compared with its comparators 9. Restoration of the impaired cGMP signalling by the PDE5A inhibitor vardenafil has been proven cardioprotective in different myocardial pathologies 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of the positive chronotropic and inotropic effects of sildenafil PDE3 is expressed in various tissues including myocardium, vascular smooth muscle, penile tissue and adipose tissue, which hydrolyzes cyclic AMP (Bischoff, 2004). Under physiological conditions, PDE3 has been proved to play an important role in regulating the automaticity and contractility primarily through the modulation of the cyclic AMP/protein kinase A signaling (Beca et al, 2011;Knight and Yan, 2012).…”
Section: Rationale Of the Doses Of Sildenafil For The Positive Inotromentioning
confidence: 99%